THE INFLUENCE OF COVID-19 PANDEMIC IN E-SAMSAT SERVICE (SAMBARA) AND THE TAXPAYER AWARENESS TO THE VEHICLE TAXPAYER COMPLIANCE (CASE STUDY AT CIMAHI CITY) PERIOD OF JANUARY - JUNE 2020 - Muhamad Bulan Rubiansah; Radzmi Damayanti; Meysa Alfhat; Muhammad Faiz An Nabil; Sendi Gusnandar Arnan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to determine the effect of Taxpayer Awareness and online tax services (e-samsatSAMBARA) on Motor Vehicle Taxpayer Compliance in the regional revenue agency of Cimahi City. The population in this study is a motor vehicle taxpayer as many as 16,947 taxpayers. The sample in this study was 125 taxpayers with a simple random sampling technique. With the method of taking data using questionnaires. The questionnaire was tested for validity and reliability, the data analysis technique in this study used the classic assumption test, multiple regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that the e-Samsat service in the covid pandemic 19 and Taxpayer Awareness Influence the Compliance of Motor Vehicle Taxpayers.